Effects of Greenselect Phytosome® on weight maintenance after weight loss in obese women: a randomized placebo-controlled study. Issue 1 (December 2016) - Gilardini, Luisa; Pasqualinotto, Lucia; Di Pierro, Francesco; Risso, Paolo; Invitti, Cecilia
Abstract Background Most subjects regain weight after weight loss due to compensatory adaptations finalized to maintain stable body energy stores. Green tea (GT) preparations, which help maintain energy expenditure while dieting could be a useful strategy to facilitate weight maintenance. The usefulness of GT preparations in weight maintenance has been poorly studied so far with conflicting results. This study evaluated if a supplement of GSP and piperine helps obese women to maintain the weight loss obtained with a 3-month lifestyle intervention. Methods In a randomized placebo-controlled study, we examined whether a highly bioavailable GT extract may counteract weight regain after weight loss. Forty obese women (age 50.1 ± 10.1 years, Body Mass Index (BMI) 36.3 ± 2.7 kg/m2 ) underwent a 3-month lifestyle intervention. At the end of the intervention, the women were randomized in two groups for the weight-maintenance phase: 20 of them were prescribed twice a day, for 3 months, with a formula containing 150 mg/dose of Greenselect Phytosome® and 15 mg/dose of pure piperine (GSP group), and 20 were given placebo (P group). Anthropometric measures and body composition were measured before (V-3) and after lifestyle intervention (V0), 1 (V1), 2 (V2), and 3 (V3) months after prescribing supplements and 3 months following the discontinuation of supplements (V6). Results Lifestyle intervention induced a significant weight reduction in both groups with similar weight change (−6.2 ± 2.6 in GSP group vs. −4.8 ± 3.1 % in P group). In the GSP group, V1 in comparison to V0, had further reduction in weight and fat mass, which remained stable at V2 and V3 and increased at V6. In the P group, weight and fat mass increased from V2 onwards. Weight changes in GSP group and P group from V0 to V3 were −1.0 kg (95 % CI −2.5 to +0.5) and + 0.3 kg (95 % CI −0.9 to +1.6), respectively. The proportion of women with weight loss ≥ 5 % was greater in the GSP group than in the P group (75 % vs. 45 % at V1, and 60 % vs. 30 % at V6, p < 0.05 for both groups). Conclusions Greenselect Phytosome® devoid of caffeine may have a clinical potential for the maintenance of weight after intentional weight loss. Trial registration Clinicaltrials.govNCT02542449 (September 2015)